Teknik Penyehatan Lingkungan Di Desa Hilizia Lauru Kecamatan Hiliserangkai Kabupaten Nias - Daeli, Serta Denius (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
The decline in environmental quality due to pollution is the impact of human behavior that does not understand the importance of protecting the environment. This problem also occurs in Hilizia Lauru Village, Hiliserangkai District, Nias Regency, where many people still do not understand environmental sanitation techniques as a whole. Sanitation facilities, lighting, air ventilation, waste management, and waste disposal still do not meet environmental health standards, so they are at risk of causing various infectious diseases and reducing the quality of life of the community. This study aims to analyze the environmental health conditions in Hilizia Lauru Village and evaluate the environmental sanitation techniques that have been implemented. The research method used is a qualitative method with a descriptive approach, involving observation, interviews, and documentation to obtain data on environmental conditions and efforts made to improve environmental health. The results of the study show that most people do not have adequate access to clean water and proper sanitation facilities. In addition, the waste management system is still traditional and poorly organized. Improvement efforts have been made through community education, construction of communal septic tanks, provision of clean water sources, and community-based waste management programs. The implementation of environmental sanitation techniques has had positive impacts, including reducing cases of environmental-based diseases and increasing public awareness of the importance of protecting the environment. However, challenges are still faced, such as limited facilities, lack of experts, and low community participation in environmental sanitation programs. Therefore, a sustainable approach is needed through collaboration between the government, health workers, and the community to create a healthier and more livable environment.